Liposomes and lipid bilayers in biosensors - Mazur, Federico; Bally, Marta; Städler, Brigitte; Chandrawati, Rona (Advances in colloid and interface science, 2017)
Biosensors for the rapid, specific, and sensitive detection of analytes play a vital role in healthcare, drug discovery, food safety, and environmental monitoring. Although a number of sensing concepts and devices have been developed, many longstanding challenges to obtain inexpensive, easy-to-use, and reliable sensor platforms remain largely unmet. Nanomaterials offer exciting possibilities for enhancing the assay sensitivity and for lowering the detection limits down to single-molecule resolution. In this review, we present an overview of liposomes and lipid bilayers in biosensing applications. Lipid assemblies in the form of spherical liposomes or two-dimensional planar membranes have been widely used in the design of biosensing assays; in particular, we highlight a number of recent promising developments of biosensors based on liposomes in suspension, liposome arrays, and lipid bilayers arrays. Assay sensitivity and specificity are discussed, advantages and drawbacks are reviewed, and possible further developments are outlined. [Display omitted] •Biosensors play a vital role in health, food and environmental monitoring•Lipid assemblies in the form of spherical liposomes or 2D planar membranes are widely used in the design of biosensing assays•Liposomes have a large internal cavity for encapsulation of signal markers and a high surface area for conjugation of recognition elements•Planar lipid bilayers are valuable for probing membrane-related biomolecular interactions•Parallel analysis of analytes (multiplexing) requires the integration of recognition elements in an array